Straw from different sorghum varieties in the formulation of new compounds for the cultivation of Pleurotus ostreatus - Siqueira, Otavio Augusto Pessotto Alves [UNESP]; Martins, Olívia Gomes [UNESP]; De Andrade, Meire Cristina Nogueira [UNESP] (Centro Universitario de Maringa, 2019)
The cultivation of the edible mushroom Pleurotus ostreatus may be performed in different substrates. No data is available on the use of sorghum wastes for mushroom production. Current study evaluates the feasibility of sorghum in the cultivation of P. ostreatus. Three treatments were tested: C1 (control, sugar cane straw), C2 (sorghum biomass) and C3 (saccharin sorghum). Treatments were composted, pasteurized and, after cooling, P. ostreatus was inoculated. Incubation and harvest occurred during two months, followed by nutrition analysis of the mushrooms and the composts' chemical analysis. Biological efficiency, loss of organic matter and mass of fresh mushrooms were evaluated. According to the substrates' chemical analysis, there was no significant difference among treatments, except humidity, where control was lower than the others. Treatments had the following productivity: C1: 1.73 kg; C2: 1.34 kg; C3: 1.07 kg. There was no significant difference for biological efficiency between treatments C1 and C2, with 69.80% and 72.76% respectively, whereas treatment C3 had the lowest biological efficiency (51.72%). Loss of organic material reached 50.56% for C1; 44.50% for C2; 40.16% for C3. Nutrition analysis of mushrooms did not reveal any significant difference among treatments, except crude fiber, where treatment C3 was higher by 18.95%, followed by treatment C2 with 16.40% and control with 14.95%.
Palha de variedades de sorgo na formulação de novos compostos para o cultivo do cogumelo Pleurotus ostreatus
Keywords: Fungi; Nutrition analysis; Productivity; Residues